An investigation into the pharmacological effects of phytocannabinoids and endocannaboids in human mesenteric arteries - Stanley, Christopher Peter (2013)
Cannabinoids cause both acute and time-dependent vasodilation/vasorelaxation in a range of vascular beds. The vascular effect of cannabinoids is dependent on the cannabinoid ligand, the species studied and the vascular bed used. To date, there have been four studies that have characterised the effects of cannabinoids in humans. Therefore, the aim of this thesis was to characterise the pharmacological effects of cannabinoids in the human mesenteric artery.